ANALISIS HADIS TEMATIK TANGGAL CANTIK DAN WAKTU BAIK DALAM MELAKSANAKAN PERNIKAHAN - Moh. Andi Asrori; Bidayatul Mutammimah (DIRAYAH : Jurnal Ilmu Hadis, 2025)
The timing of weddings has recently moved from classic models such as using weton and primbon to a more modern model by looking for beautiful dates based on good numbers or the birthdays of the bride and groom. On the other hand, basically Rasulullah SAW, through his hadith, has signaled good times. This study aims to analyze the good time according to the hadith in relation to the beautiful date. This research is included in the type of literature research with descriptive analysis method. The results of this study, first, the sunnah of getting married in the month of Shawwal is based on the hadith which explains that Siti Aisyah and Rasulullah SAW got married in that month. The hadiths that specifically explain the recommendation to marry on Friday cannot be found in the as-sittah and at-tis'ah poles. However, because there are many hadiths that explain Friday as full of blessings, scholars interpret that Friday marriage is sunnah. As for getting married in the month of Safar, it is based on the history of Siti Fatimah's marriage to Ali bin Abi. Second, although there are several good times that are recommended for marriage based on the hadith of the Prophet SAW, that does not mean that getting married other than that time is prohibited and contradicts the hadith. It is permissible to marry on a beautiful date as long as first, one does not believe that other than that date is an unlucky date, second, the beautiful date is determined by the two bridal couples not obtained from normal paras, third, does not conflict with general customs recognized by sharia.